Effectiveness increasing of premises lighting system of engineers and aviation airport centre - Зеленков, І.А.; Мисюк, Ю.П. (Proceedings of National Aviation University (archive), 2004)
In article features of illumination of premises rooms of the engineering - aviation center are analysed, recommendations on improvement of system of illumination are made with the purpose of decrease in fatigue working, increases in visual and general serviceability of the person and increase of labour productivity.